Avaliação do desempenho da Hidroeléctrica de Cahora Bassa (HCB), S.A.: criação de valor económico para o accionista - Maunde, Nonávio André David (2021)
The present work develops the business performance evaluation model based on the creation of economic value for the shareholder, contributing a little more to a topic that is rarely addressed in Mozambique. This performance evaluation system is a crucial tool for management, not only in terms of its meaning, but also in terms of the best form of evaluation. The main idea behind these models, is that the company's objective is not only to produce profit, but a result that exceeds the expectations of shareholders' remuneration, which leads to the continuity of an enterprise, its ability to overcome market challenges, grow in competitive environments, and create wealth for its shareholders. Regarding the methodological aspects, the research used a descriptive methodology, in the case study format, with a quantitative approach. In the case study carried out, the analysis fell on a national reference company in the hydroelectric sector, in this case, Hidroeléctrica de Cahora Bassa, S.A., from 2014 to 2016, collecting the relevant financial information contained in the annual reports and accounts. In this perspective, several models have been developed (based on economic value) that allow assessing whether or not the entity is creating economic value for shareholders, which implied reviewing other traditional valuation models based on book value. As a metric for evaluating performance based on economic value, particular emphasis was placed on the study of EVA, CVA and LE. The results of the study showed that the performance of the company calculated by the traditional methods was positive in all periods of the series under analysis, however, it was negative by the methods based on the economic value, which reflects the activity of the company was not able to generate sufficient income to compensate capital investors, that is, the company was destroying the shareholders' wealth.